The effect of cadet resilience on self-efficacy and professional achievement: verification of the moderated mediating effect of vocational calling - Navickienė, Olga; Vasiliauskas, Aidas Vasilis (Frontiers in Psychology, 2024)
Background The primary objective of this study was to empirically examine the influence of cadets’ resilience on their professional achievement within the unique context of a Military Academy. In doing so, the study sought to delineate the role of self-efficacy as a key mediator in the intricate relationship between the resilience of cadets and their professional achievements. The main focus of this study was to clarify the causal and effect relationships between the psychology and behavior mechanisms of the cadets. This was achieved through rigorous scrutiny of the moderated mediating effect of vocational calling within the multifaceted relationship involving cadets’ resilience, self-efficacy, and professional achievement. Methods The study’s participant pool consisted of 121 individuals, comprising cadets in their third and fourth years of study, all of whom aspired to attain the rank of officer within the Military Academy. To rigorously investigate the hypotheses presented, a series of causal relationships among the four core variables were evaluated using a robust regression analysis methodology. To facilitate this analysis, the PROCESS macro 3.5v, a Hayes-developed tool, was effectively used. Results The findings of this study revealed several critical insights. First, vocational calling emerged as a potent moderating factor in shaping the relationship between cadets’ resilience and self-efficacy. Furthermore, it was demonstrated that vocational calling exerted a conditional influence on the impact of cadets’ resilience on their professional achievement, with self-efficacy serving as a crucial mediating mechanism in this relationship. In particular, the study affirmed that self-efficacy functioned as a comprehensive mediator, elucidating the pathway through which the resilience of the cadets ultimately influenced their professional achievements. Conclusion The results of this research contribute significantly to enhancing our understanding of the intricate connection between the resilience levels exhibited by cadets and their corresponding professional achievements. Furthermore, these findings have valuable implications for the ongoing refinement of military education and training programs. They offer insights that could inform the development of more effective testing and selection protocols for military personnel, ultimately benefiting the armed forces in their pursuit of excellence.